Resposta :
[tex]f(x) = 2x {}^{2} - 6 \: \: \: \: \: \: \: \: \: \: \\ 0 = 2x {}^{2} - 6 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ - 2x {}^{2} = - 6 \: \: \: \: \: : ( - 2) \\ x {}^{2} = 3 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \boxed{\boxed{\boxed{x = ± \sqrt{3} }}} \: \: \: \: \: \: \: \: \: \: \: \: \: \: [/tex]
atte. yrz
Explicação passo-a-passo:
[tex]f(x) = 2x {}^{2} - 6[/tex]
[tex]2x {}^{2} - 6 = 0[/tex]
[tex]2x { }^{2} = 6[/tex]
[tex]x {}^{2} = \frac{6}{2} [/tex]
[tex] x {}^{2} = 3[/tex]
[tex]x = ( + ou - ) \sqrt{3} [/tex]